The Political Economy of Decentralization Reforms : Implications for Aid Effectiveness - Eaton, Kent (World Bank, 2012)
This volume presents a preliminary framework designed to help international development partners consider the relevance of political economy issues for their programmatic support to decentralization and local government reform. The intention is neither to advocate decentralization in general or in any particular form, nor to presume or privilege any particular decentralization objective. Instead, the purpose is to document the potential value of better understanding how (primarily national and intergovernmental) political and institutional dynamics do or could affect the scope for realizing decentralization reforms aligned with commonly advocated service delivery, governance, and poverty reduction goals. The underlying premise is that systematic analysis of these issues can productively complement the dominantly technical diagnostic work typically carried out by development partners. Specifically, development partners can benefit from better understanding the practical significance of motives that drive politicians and bureaucrats to support or oppose reform at various stages of the decentralization process, from making an initial reform decision to detailed design and implementation. In addition, the framework addresses how these incentives can weaken, strengthen, or shift in response to changes in political and economic conditions that arise after reform begins. A general approach to conducting political economy of decentralization analysis is outlined, recognizing the need to tailor such analysis to the particular country context. This volume is based on literature reviews and knowledge derived from selected country experiences.